The Adult Educator and his Self-Efficacy - Μαγγόπουλος, Γιώργος; Μουρατίδης, Χρήστος (Education Sciences, 2022)
The current work aim at indicating the views on the learners in Training Programs for Adult Education regarding the role and the qualifications for the adult trainer and their self-efficacy. Atmethodological level , the research was based on the case study and the data collection came from conducting semi-structured interviews having 20 participants as a sample. All the interviews were personal having open – ended questions. Regardingthe research findings multidimensional role giving importance to the methods and the practices that he should adopt. The knowledge of the subjectisconsideredas a significant advantage giving self-confidence to the participants in order to correspond in future to their role as adult educators. They indicate trust to the training and the believe that the acquired knowledge and skills contribute to their career